Ecology of Meimuna mongolica (Hemiptera: Cicadidae) Nymphs: Instars, Morphological Variation, Vertical Distribution and Population Density, Host-Plant Selection, and Emergence Phenology. Issue 1 (14th April 2015) - Hou, Zehai; Li, Qinglong; Yang, Mingsheng; Liu, Yunxiang; Wei, Cong
Abstract : The cicada Meimuna mongolica (Distant) (Hemiptera: Cicadidae) is one of the most important pests of economic forest in Guanzhong Plain of Shaanxi Province, China. Information about ecological characteristics and some sustainable control measures of this species is urgently required for its control. In this study, nymphal instars, morphological variation, vertical distribution, and population density in soil, and emergence phenology of nymphs of M. mongolica on three main host plants ( Pinus tabuliformis Carr., Populus tomentosa Carr., and Pyrus xerophila Yü) were studied, based on combined morphological and molecular identification, investigation of the first-instar nymphs hatched from eggs and others excavated from soil, and investigation of exuviae in the adult emergence period. Five nymphal instars of M. mongolica were redetermined according to the distribution plots of the head capsule widths of the nymphs. Nymphs of third and fourth instars showed morphological variation, which is closely related to host-plant association. The mean densities of nymphs in soil under the three host plants were significantly different, indicating a distinct host preference. The nymphs could extend their distribution from the 0–10 cm soil layer to the 51–60 cm soil layer underground but not beyond 60 cm soil layer under all the three host plants. The 21–30 cm soil layer under all the three host plants has the highest nymphal population density. The sex ratio of the entire population was nearly 50:50, but males dominated in the early half of the duration of the emergence. These ecological characteristics of M. mongolica could provide important information for sustainable control measures.